Spatial distribution of cetaceans in the Bay of Biscay and implications of the Marine Strategy Directive for their conservation - Andrade Marina Isabel Laborde Basto de (2008)
Tese de mestrado, Biologia (Biologia da Conservação), 2008, Universidade de Lisboa, Faculdade de Ciências Resumo alargado disponível em português European seas are subjected to continuous degradation and cetaceans, in particular, are vulnerable to several threats, being the fisheries bycatch and the climate change the greatest ones. The Bay of Biscay has been found to be the centre of highest cetacean diversity in the Northeast Atlantic. In response to these problems concerning the state of the marine environment, in June 2008, the UE established the Marine Strategy Framework Directive (MSFD), which aims to achieve a good environmental status' by 2020. Hence, a requirement arises for ecological indicators based on an ecosystem approach. In this context, this study, relying on data from CODA project, proposes to investigate the summer spatial distribution of cetaceans in the offshore waters of the Bay of Biscay, using physiographic and remotely-sensed oceanographic variables. During the survey, 13 cetacean species were identified, being the most frequent, the fin whale and the common dolphin. A higher species richness was evident over the submarine canyons. Distribution of the three most sighted species (fin whale, common and striped dolphins) was modelled spatially, using generalised additive models, in relation to environmental features. Spatial segregation was clear, with dolphins distributed in the inner part of the Bay, and the whales towards West with special incidence around the Galician Bank. These results permit the identification of potential cetacean hotspots' in the Bay of Biscay region, enabling the establishment of marine protected areas. Cetaceans do have a great potential to act as indicator species and may be valuable assets for planning, promoting, and implementing MPAs. Their use as ecological indicators should be accomplished with other studies where different metrics are applied, also based on other taxonomic groups, which combined will provide a comprehensive panorama of the ...